Fifty years of smelling sulfur: From the chemistry of garlic to the molecular basis for olfaction. (1st February 2017) - Block, Eric
GRAPHICAL ABSTRACT: ABSTRACT: The striking difference in odor threshold of low molecular weight thiols compared to analogous alcohols has been investigated by isolation and study of human olfactory receptors responsive to these thiols. It has been discovered that human thiol receptor OR2T11 responds specifically to gas odorants ethanethiol and 2-methyl-2-propanethiol, as well as to related low molecular weight thiols, and requires ionic copper for its robust activation. When OR2T11 is screened against a series of alcohols, thiols, sulfides and metal-coordinating ligands, it responds, with enhancement by copper, to four-membered cyclic sulfide thietane, to one- to four-carbon straight-, branched-chain and five-carbon branched-chain thiols, and to the mouse semiochemical CH3 SCH2 SH and derivatives, but not to longer chain thiols, suggesting compact receptor dimensions. Alcohols and hydrogen sulfide are unreactive.